FAKTOR YANG MEMPENGARUHI PERILAKU MEROKOK PESERTA DIDIK DI SMA NEGERI 12 PADANG - Fadrizal, Hendri; Kasih, Fitria; Yulastri, Weni (Bimbingan dan Konseling, 2013)
The studentsâ aims to examine the factors that influence smoking behavior of students at SMA Negeri 12 Padang, by describing the following factors 1). Factors influence parental attention in smoking behavior of students in 12 high schools in Padang. 2). Factor of peer influence on smoking behavior of students at SMA Negeri 12 Padang, 3). Personality factors influence the smoking behavior of students at SMA Negeri 12 Padang and 4) tobacco advertising influence factors in smoking behavior of students at SMA Negeri 12 Padang. This research is a descriptive study. The study population was all students of SMA Negeri 12 Padang in the academic year 2011/2012 who smokes. Total sampling techniques sampling as many as 36 people. Source of data used are primary data obtained from the respondents surveyed are learners. The instrument used in this study was a questionnaire. As for the use of data analysis techniques percentage. The results of this study can be described as follows: 1) factors influence parental attention to smoking behavior of students at SMA Negeri 12 Padang is included in many categories, namely the average percentage of 68.56%, 2) factors influence the behavior of peers smoking students in 12 high schools in Padang is included in many categories, namely with an average percentage of 68.43%, 3) personality factors influence the smoking behavior of students at SMA Negeri 12 Padang is included in many categories, namely the percentage average of 68.44% and 5) factors influence tobacco advertising in smoking behavior of students at SMA Negeri 12 Padang is included in many categories, namely with an average percentage of 71.30%. This means that: Factors that influence the smoking behavior of students at SMA Negeri 12 Padang included in many categories. Based on the above results the authors suggest to parents and teachers in schools to provide information about the dangers of smoking to the learners.